1998
DOI: 10.1002/(sici)1097-4636(19980605)40:3<425::aid-jbm13>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic, transmission electron microscopic, and confocal laser scanning microscopic observation of fibroblasts cultured on microgrooved surfaces of bulk titanium substrata

Abstract: During this study, microtechnology and plasma etching were used to produce gratings 1.0 (TiD01), 2.0 (TiD02), 5.0 (TiD05), and 10.0 m wide (TiD10) into commercially pure titanium wafers. After incubation of rat dermal fibroblast (RDFs) on these surfaces for 3 days, the cells were observed with scanning electron (SEM), transmission electron (TEM), and confocal laser scanning microscopy (CLSM). Results showed that the RDFs as a whole and their stress fibers oriented strictly parallel to the surface pattern on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
2
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 8 publications
5
21
2
2
Order By: Relevance
“…Our data suggest that the cells cultured in collagen gel dot colonies on the microgrooved surfaces were well aligned, but lower in density, less spread, and longer and narrower in shape than those grown on the control surfaces. These observations are in general agreement with those of other investigators 3, 15, 24, 32–35, 40–43, 50–63. The in vitro effects of microgrooved substrates are probably based on relationships between microgroove dimensions and the abilities of cells to attach, spread, and migrate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data suggest that the cells cultured in collagen gel dot colonies on the microgrooved surfaces were well aligned, but lower in density, less spread, and longer and narrower in shape than those grown on the control surfaces. These observations are in general agreement with those of other investigators 3, 15, 24, 32–35, 40–43, 50–63. The in vitro effects of microgrooved substrates are probably based on relationships between microgroove dimensions and the abilities of cells to attach, spread, and migrate.…”
Section: Discussionsupporting
confidence: 92%
“…However, our observations of stress fibers in 4‐day control cultures suggests that cell source or microgroove depth most likely caused these disparate results. The distribution of focal adhesions in our NIH‐3T3 fibroblasts cultured on microgrooved substrates was in general agreement with these investigators' observations that focal adhesions were limited to areas of cell‐substrate contact 24, 55, 61…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have reported the alignment of cells with parallel groove formations23 and alterations in cell morphology between smooth and featured areas 24. Furthermore, Singhvi, Stephanopolous, and Wang25 and den Braber et al26 reported differences in cell alignment and attachment for features above and below 50 μm in size, as seen in this study, and Walboomers et al9 observed preferential cell attachment to surface ridges, also as seen in this work. However, more detailed confirmation of this preferential attachment through further techniques such as cross‐sectional imaging is needed.…”
Section: Discussionsupporting
confidence: 83%
“…The Brunette studies all used percutaneous parts that were made of nonflexible epoxy material, which was titanium‐coated. It is known that silicone and titanium are different with respect to many surface chemical properties, for instance, it has already been described that different protein adsorption and cell attachment reactions are seen on different materials and that the surface chemistry always interacts with microtopography 3, 20. There is always an interplay between the chemistry and the topography of the materials.…”
Section: Discussionmentioning
confidence: 99%